Recent Progress in Photocatalytic Antibacterial - Zhou, Ziling; Li, Bo; Liu, Xiangmei; Li, Zhaoyang; Zhu, Shengli; Liang, Yanqin; Cui, Zhenduo; Wu, Shuilin (ACS applied bio materials, 2021)
Pathogens on wounds and infected tissues or pathogens in drinking water or public facilities have been doing great harm in human life. Because of booming drug resistance and superbacteria, the abuse or excessive use of antibiotics during systemic treatment has caused a global antibiotic crisis. However, it usually takes a long time to develop antibiotics. In recent years, photocatalytic antibacterial agents have no drug resistance and side-effects due to their rapid and efficient bactericidal efficacy. They are becoming one of the most hopeful substitutions to antibiotics for dealing with the bacterial diseases and water pollution caused by certain pathogens. Photocatalysis has unique advantages in the field of antibacterials, and its controllability plays an irreplaceable role. This review focuses on the mechanism of photocatalysis, which involves representative photocatalytic semiconductors (metal oxides, metal sulfides, carbon nitride, heterojunction composite materials) and organics (organic polymers and organic small molecules-aggregation induced emission) as well as their photocatalytic antibacterial mechanism. In this paper, we summarize the photocatalytic antibacterial mechanisms by the numbers and current developing of photocatalytic antimicrobial materials applications. Current difficulties and expectations for the future in these fields are presented to stimulate the developing of material manufacturing technologies and their industrialization to combat bacterial infections. In addition, potential application limitations and future research potential are highlighted.